2022
DOI: 10.3822/ijtmb.v15i4.739
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of a Single-Session of Full-Body Foam Rolling on Heart Rate Variability

Abstract: Background: Self-myofascial release has been demonstrated to increase relaxation and improve blood flow, yet it is unknown if it can elicit an acute effect on heart rate variability (HRV). Purpose: This study aimed to determine if a single-bout of foam rolling could increase parasympathetic activity as measured by HRV. Methods: Twenty (20) participants volunteered and their baseline HRV was assessed using a finger sensor while lying supine, and then a second measure was recorded with them sitting upright with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Another study by Delaney et al ( 2002 ) also reported increased HF at 5 and 20 min after myofascial trigger point massage therapy sessions. Similar to our study Kopec et al ( 2022 ) found no significant effects of a full-body SMR session on RMSSD.…”
Section: Discussionsupporting
confidence: 92%
“…Another study by Delaney et al ( 2002 ) also reported increased HF at 5 and 20 min after myofascial trigger point massage therapy sessions. Similar to our study Kopec et al ( 2022 ) found no significant effects of a full-body SMR session on RMSSD.…”
Section: Discussionsupporting
confidence: 92%